(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This article presents a case study conducted at Jigawa State College of Education and Legal Studies Ringim to examine the implementation and effectiveness of inclusive education policies. The study employed a qualitative research design, including interviews, focus group discussions, and document analysis, to gather data from educators, administrators, and students. The findings highlight the challenges faced in implementing inclusive practices and the impact of inclusive education policies on student learning outcomes. The article concludes with recommendations to enhance the implementation and effectiveness of inclusive education policies at the college.